(untitled) (Bangladesh Journal of Botany, 2024)
Salt stress has been identified as a vital limiting factor affecting rice output across the world. In rice, the salt tolerance nature is complicated, since it is dependent on different components and is lowly heritable. Consequently, it is a key method to breed salt-tolerant varieties for improving rice output upon salt stress. To investigate the genetic foundation for salt stress tolerance of rice seedlings (Oryza sativa L.), bulked segregant analysis coupled with whole-genome sequencing (BSA-seq) was performed in QTL mapping on the huge F2 population including totally 2,500 plants obtained through crossing the indica rice variety 1892S with the japonica rice variety Huaidao 5 (HD5). In BSA-seq, only extremely-sensitive (ES) and extremely-tolerant (ET) seedlings were utilized, making it not difficult for identification with no requirement of quantitative analysis. Therefore, the seedling survival state was an appropriate indicator trait in BSA-seq. HD5 in seedling stage exhibited enhanced tolerance to extended salt stress when compared with 1892S. The DNA pools prepared based on 235 ES together with 165 ET seedlings of F2 population through block regression mapping (BRM) were analyzed, and a QTL was mapped onto chromosome 3 and termed QTL qSLST3.1. There were numerous rice salt tolerance-associated QTLs on chromosome 3 in seedling stage, but just one was situated in the confidence interval of qSLST3.1. These QTLs did not have identical positions. So qSLST3.1 should be the new QTL. Moreover, our results can shed more lights on marker-assisted salt-resistant variety breeding and positional cloning of rice salt tolerance trait-related genes. Bangladesh J. Bot. 53(2): 405-410, 2024 (June)